Constituency Campaigning and Canvassing for Support at the 2011 National Assembly of Wales Election. (February 2016) - Johnston, Ron; Pattie, Charles; Scully, Roger; Cutts, David
An increasing volume of research has suggested the efficacy of get-out-the-vote campaigns in the UK: having identified its potential supporters, a party then contacts them to encourage them to turn out on election day, and those contacted are more likely to reward the party by voting for it than are those not contacted. This article illustrates these findings with data from the 2011 Welsh Election Study. Each of the four main parties concentrated its attention on those who voted for it at the previous contest in 2007; those contacted – especially those contacted via media other than leaflets – were more likely to vote for the party again in 2011 than those who were not contacted.